26.8k views
5 votes
Find the value of x → x² = (Q - A)(Q - B)(Q - C) ….. (Q - Z)

User Garrow
by
5.8k points

2 Answers

0 votes

Answer:

t8y8 uv7g7 ug8 ugy ug h 7 v jvu utyc7 . hit u ut taj h

Explanation:

fucjvjvi j jvu jvivu igigi ivigi iigihi ivigi igih

User Raynos
by
5.8k points
4 votes

Answer:


\boxed{0}

Explanation:

x² = (Q - A)(Q - B)(Q - C) ... (Q - Z)

x² = (Q - A)(Q - B)(Q - C) ... (Q - P)(Q - Q)(Q - R) ... (Q - Z)

x² = (Q - A)(Q - B)(Q - C) ... (Q - P)(0)(Q - R) ... (Q - Z)

x² = 0

x = 0

User Himanshu Aggarwal
by
4.7k points